Food insecurity amongst older people in the UK - Purdam, K; Esmail, A; Garratt, E (Emerald Publishing Limited, 2019)
Purpose The purpose of this paper is to present findings from research into food insecurity amongst older people aged 50 years and older in the UK. Design/methodology/approach This paper uses secondary analysis of national-level survey data and semi-structured interviews with older people receiving emergency food from foodbanks. Findings There is a forgotten care gap in the UK where a substantial number of older people are living in food insecurity. Many older people live alone and in poverty, and increasing numbers are constrained in their spending on food and are skipping meals. Food insecurity amongst older people can be hidden. Within families a number of older people were trying to ensure that their children and grandchildren had enough to eat, but were reluctant to ask for help themselves. Research limitations/implications The broad categorisation of older people aged 50 and above comprises people in very different circumstances. The qualitative component of the research was undertaken across various sites in a single city in England. Despite these limitations, the analysis provides important insights into the experiences of the many older people enduring food insecurity. Practical implications An increased public and professional awareness of food insecurity amongst older people is needed. Increased routine screening for under-nutrition risk is a priority. Policy initiatives are needed that are multifaceted and which support older people across a range of age groups, particularly those living alone. Social implications Food insecurity amongst older people in the UK raises questions about the present policy approach and the responsibilities of the government. Originality/value The research provides important new insights into the experiences of the many older people experiencing food insecurity in the UK by drawing on survey data and interviews with older people using foodbanks.